Waiting for Max : a NICU story - Rosen, Emily (Collective Book Studio, 2025)
Louise can't wait to meet her new little brother, Max! But he arrives earlier than expected and must stay in the neonatal intensive care unit (NICU) until he's strong enough to come home. Waiting is hard. Really hard. So Louise uses her BIG imagination to dream up creative plans to bring Max home.